Biomarkers in breast cancer. Part I: receptors, growth factors, genes and oncogenes - Ślubowski, Tadeusz; Ślubowska, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2007)
The first part of this two-part review of established and emerging breast cancer biomarkers considers up-to-date knowledge and describes new types of prognostic and predictive biomarkers, with diagnostic and therapeutic applications in the experimental and clinical milieu. It also discusses new perspectives for utilizing cell cycle markers, growth factors, oncogenes, suppressor genes and cell adhesion markers as prognostic methods in breast cancer development. It outlines efforts for achieving high sensitivity and specificity of biomarkers permitting to detect high risk groups, evaluate the progress of the disease and treatment outcomes. Struggles against formal and technical setbacks hampering the full introduction of biomarkers into the clinic, as takes place in case of microarray techniques, are also described.